Pemberian Makanan Sehat “Nutrisi Seluler” terhadap Produktivitas Kerja pada Karyawan Penggilingan Padi - Aprina Aprina (Jurnal Kesehatan, 2017)
The current diet of various cultural influences, technology, lifestyle greatly affects human health in general in various countries. According to WHO statistics, 70% of premature deaths, caused by diabetes, cancer, heart attack and stroke, 50% are associated with poor diet or lack of nutrition. Rice millers began to stand in 1980, from the beginning employ 10-15 employees per day, if there is a demand to grind 20 tons of rice per day then the workforce increases to meet the target to 40 workers per day. The purpose of this research is to know the effect of Nutrition Cellular on the productivity of rice mill worker of HANESCA Subdistrict of Purbolinggo East Lampung. Design of experimental research with nonrandomized design Pre Test Post Test Contro Group Design, research sample examined physical condition, selected from labor that has been measured IMT with the number of 15 respondents. The statistical test used in this study is a dependent t-test that aims to examine the differences between the two treatment groups before and after the administration of Nutrition Cellular. The result of research Average of work productivity of employees before given Nutrition Cellular equal to 5910,53, average work productivity of employees after given Cellular Nutrition equal to 6,784 kg per day, there is an effect of Nutrition Cellular to employee work productivity p-value value 0,041. Suggestions that the company can cultivate healthy food Nutrition Cellular as a source of nutrients can be followed by all companies both public and private because it is very good to provide energy and protein that has met the needs of labor.